Application of Particle Swarm Optimization for Optimizing the Process Parameters in Turning of PEEK CF30 Composites. (2016) - Hanafi, I.; Cabrera, F. Mata; Dimane, F.; Manzanares, J. Tejero
Abstract: This work deals with optimization of multiple characteristics in Computer Numerical Control (CNC) turning of reinforced Poly Ether Ether Ketone (PEEK CF30) with TiN coated tools under dry condition. The considered criteria included specific cutting pressure, machining force and cutting power. Three controllable factors of the turning process consisting of cutting speed, depth of cut and feed rate were incorporated. Taguchi design of experiments method was used to arrange the experimentation task. The developed response surface models were then employed with particle swarm optimization (PSO) to optimize the cutting conditions. PSO program gives the minimum values of the considered criteria and the corresponding optimal cutting conditions.